Using PLS-SEM to build an employability confidence model for higher education recipients in the field of business studies. Issue 9 (7th October 2019) - Nicolescu, Luminita; Nicolescu, Ciprian
Abstract : Purpose: This paper aims to present a model of the employability confidence of graduates using employability skills. The purpose of the study is twofold: to identify to what extent self-perceived employability skills (input employability) influence the employability confidence of students/graduates (output employability) and to identify if there are determinant relationships between categories of employability skills. Design/methodology/approach: The researchers for this study built and tested an employability confidence model which included seven constructs. Six focussed on employability skills "professional skills, transferable individual skills, transferable social skills, personal qualities, job seeking skills and corporate work-related skills", while the last one focussed on employability confidence, seen as the students'/graduates' self-reliance for getting and maintaining a job. The model was refined using structural equation modelling (with SmartPLS 3 SEM software) and was tested by empirically, analysing a sample of participants studying business. Findings: The results illustrated that four categories of skills (personal qualities, professional skills, job seeking skills and transferable social skills) have a positive and significant influence on students'/graduates' employability confidence, while individual transferable skills and corporate-related skills do not have a significant influence on employability confidence. Research limitations/implications: The study contributed to the exiting literature by proposing a new model and measurement instrument that links input employability (individual employability skills) with output employability (employability confidence). The model emphasizes the complete range of individual employability skills, the types of skills that are in the control of the individual. It also contributed by collecting data from a less studied country and region, Romania, that can be considered relevant for Central and Eastern Europe due to similar economic, political, cultural and historical characteristics. Practical implications: From a practical point of view, the results can be of interest to individuals, to universities and the teaching staff, to organizations and their human resource specialists, and to public administrators, as they all can act to support the development of individual employability skills, thereby helping to increase the employability confidence of individuals. Originality/value: The study contributed to the exiting literature not only by proposing a new conceptual model to analyse employability confidence but also by collecting data from a less studied region, Romania, that can be considered relevant for Central and Eastern Europe due to similar economic, political, cultural and historical characteristics.